CircASPH Promotes Hepatocellular Carcinoma Progression Through Methylation and Expression of HAO2 - Zhuo, Han; Xia, Jinguo; Zhang, Jin; Tang, Junwei; Han, Sheng; Zheng, Qitong; Zhu, Deming; Zhang, Feihong; Xu, Zhenggang; Sun, Dongwei; Tan, Zhongming; Wu, Chen (Frontiers in Oncology, 2022)
CircRNAs have been reported to be related to hepatocellular carcinoma (HCC) development. Limited studies have revealed the expression profile of circRNAs in tumor and paratumour normal samples in HCC patients. We found that circASPH was significantly increased in HCC tumor samples and that the level of circASPH was closely related to the overall survival (OS) of HCC patients. Mechanistically, circASPH could regulate the methylation of promoter and gene expression of Hydrocyanic Oxidase 2 (HAO2) to promote HCC progression by acting as a sponge for miR-370, which targeted the DNMT3b and increased the 5mC level. In summary, our study determined that circASPH could promote the methylation and expression of HAO2 and could be considered an important epigenetic regulator in HCC progression.